The relationship between body condition score and backfat in gestating sows - Young, M.G.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Backfat and body condition score were measured on 731 sows in a commercial swine facility to assess the accuracy of feeding sows in gestation based on body condition score. Body condition score was poorly correlated (r2 = 0.19) with backfat thickness. For example, sows assessed with a body condition of 3 ranged in backfat from 0.3 to 0.9 in. (7.5 to 23 mm). This illustrates the need to find a more objective method of measuring body condition (such as ultrasound) in order to properly adjust feeding levels and thus reduce variation in backfat of sows.
Keywords: Swine; Sows; Backfat; Body condition score